Power Measurement in Doubly Fed Induction Generator Wind Turbine - Rishabh Sharma, (Journal of Power Electronics and Devices, 2020)
This paper presents a matrix associated wind power age plot utilizing a Doubly Fed Induction Generator (DFIG). This can supply power at the steady voltage and consistent recurrence with the rotor speeds differing. This makes it reasonable for variable speed wind vitality applications. The DFIG framework comprises of the wind turbine, non-concurrent wound rotor enlistment generator, and controller [2]. In which the stator is associated straightforwardly to the lattice and the rotor twisting is in interface with rotor converter and framework converter. The utilization of consecutive converter in the rotor circuit brings about low twisting current, responsive force control, and work at variable speed. Numerical displaying of the DFIG is done to dissect the exhibition of the frameworks and they are recreated utilizing MATLAB. The reproduction results for the framework are acquired and thus it shows that the framework can work at variable speed with low symphonious current contortion. The goal is to track and concentrate the most extreme force from the breeze vitality framework and move it to the network for valuable work.